Óleos essenciais de tangerinas para manejo de podridão floral dos citros (Colletotrichum abscissum) - Zunkeller, Andreza Bonetto (Universidade Federal de São Carlos, 2024)
Citrus farming in Brazil has been facing phytosanitary problems that lead to significant production losses, among which postbloom fruit drop (PFD) caused by the fungus Colletotrichum abscissum stands out. This study aimed to investigate the action of tangerine essential oils (EOs) on the fungus C. abscissum for the management of CBF. EOs of three tangerine varieties: IAC 2019Maria mandarin, Murcott IAC 221 tangor and Late IAC 585 willowleaf, extracted from unripe and ripe fruits at different dosages (0; 2; 4; 8; 16 and 32 (µL mL-1) were evaluated for the percentage of inhibition of mycelial growth, speed index and area under the mycelial growth curve, sporulation and germination of in vitro spores of the fungus C. abscissum. In addition, the chemical components present in the EOs and the yield and their relationship to the diameter of the fruits and peel thickness were verified. Given the results found in vitro, the disease control capacity in detached flowers of Tahiti acid lime was analyzed, in addition to the potential of the EOs to activate defense mechanisms in plants, by the action of peroxidase, polyphenol oxidase and phenylalanine ammonia-lyase. Limonene was the main compound found in the EOs of tangerines extracted from unripe and ripe fruits. It was observed that the Late IAC 585 willowleaf presented a higher EO yield when extracted from unripe fruits. There was a positive correlation between yield and epicarp thickness of the peel for both EOs from unripe and ripe fruits. In the in vitro test with EOs extracted from unripe fruits, the Late IAC 585 willowleaf demonstrated a greater capacity to inhibit mycelial growth and when using the EO extracted from ripe fruits, the IAC 2019Maria mandarin was more efficient in controlling the pathogen. The EOs of both varieties were effective in controlling sporulation when extracted from unripe fruits. For ripe fruits, there was a difference only between dosages, with a sharp decrease in the number of conidia with increasing dosage. The EO of the IAC 2019Maria mandarin stood out for presenting control of spore germination at lower doses, when compared to the other varieties, for both unripe and ripe fruits. When applied to detached flowers, the EO had no systemic action on the flowers to prevent C. abscissum infection, in addition to not having the ability to activate the plant's defense mechanisms.
Tangerine essential oils for management of postbloom fruit drop (Colletotrichum abscissum)
Keywords: Citricultura; Efeito antifúngico; Crescimento micelial; Compostos voláteis; Controle alternativo; Citrus spp; Citrus farming; Antifungal effect; Mycelial growth; Volatile compounds; Alternative control; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA